Pemanfaatan Limbah Plastik Melalui Inovasi Ecobricks di Desa Setia Tawar Barat - Lestari, Bunga; Yumni, Auffah; Ramadhani, Cinta; Adelya Putri, Fatin; Syifa Salsabila, Nada; Haviza Purba, Nadia; Azzuhra Fadhillah, Siti; Rizki Wardani Simanjuntak, Sri; Syahfitri, Yunita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Plastic waste is a type of waste that is very difficult to decompose and can cause land and water pollution and endanger human health and marine life. The uncontrolled accumulation of plastik waste can contribute to a variety of complex environmental problems. This research aims to investigate the use of plastik waste as a form of environmental responsibility, with a focus on making ecobricks in Setia Tawar Barat village. The method used is a descriptive experimental approach which involves several stages, namely collecting plastic waste from households and industry, cleaning the waste, cutting it into small parts, and filling used plastic bottles until they are solid to form ecobricks. The research results show that making ecobricks can significantly reduce the volume of plastik waste that ends up in landfills, as well as providing benefits as an economical and long-lasting alternative construction material. Apart from that, this research also evaluates the social and environmental impacts of using ecobricks, such as increasing public awareness of the importance of processing plastic waste and reducing the carbon footprint. Innovations in processing plastic waste were also identified, such as the use of ecobricks in various construction applications such as building walls, furniture and community infrastructure. This research also highlights the importance of active participation from various stakeholders, including society, government, and industry, in supporting ecobricks initiatives. Thus, the conclusion of this research is that ecobricks are an effective and environmentally friendly solution in overcoming the problem of plastic waste, and have great potential to be widely adopted as part of an integrated sustainability and waste management strategy. Through education and ongoing community involvement, ecobricks can be a way to reduce the negative impact of plastic waste on the environment and living creatures.